2022
DOI: 10.1532/hsf.4277
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Rarefaction and Myocardial Fibrosis in Hypertrophic Obstructive Cardiomyopathy: A Histopathological Comparison of Pediatric and Adult Patients

Abstract: Background: Hypertrophic obstructive cardiomyopathy (HOCM) is a genetic cardiomyopathy characterized by microvascular ischemia and myocardial fibrosis. Microvessels play an important role in myocardial fibrosis in HOCM. However, the changes of myocardial microvessels and myocardial fibrosis in pediatric and adult patients with HOCM remain unclear. This study was to investigate the changes in myocardial microvessel density (MVD) and myocardial fibrosis in pediatric and adult patients with HOCM. Methods: We anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Therefore, activated SMAD signaling may be the direct cause of the fibrotic outcome of HOCM. And in our previous study, we found that patients with HOCM had reduced microvascular density and impaired myocardial perfusion 4 . The main role of MMP is to degrade type I and III collagen, and its elevated activity can cause increased fibrillar collagen degradation, extracellular matrix remodeling, and ventricular dilation 28 .…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Therefore, activated SMAD signaling may be the direct cause of the fibrotic outcome of HOCM. And in our previous study, we found that patients with HOCM had reduced microvascular density and impaired myocardial perfusion 4 . The main role of MMP is to degrade type I and III collagen, and its elevated activity can cause increased fibrillar collagen degradation, extracellular matrix remodeling, and ventricular dilation 28 .…”
Section: Discussionmentioning
confidence: 78%
“…Some studies confirmed the high burden of myocardial fibrosis in both young patients who suffered sudden cardiac death 2 or older patients with HOCM suffering from advanced heart failure 3 . Our previous histopathological study demonstrated that pediatric patients with HOCM may present with severe myocardial fibrosis and reduced microvascular density 4 .…”
Section: Introductionmentioning
confidence: 98%
“…Numerous studies have measured the density of small vessels in hypertrophied HCM septal/LV tissue samples and have found this to be 21–44% lower than in control patients [ 54 , 56 , 57 , 60 63 ]. With no convincing association with genotype [ 61 ], reductions in small vessel density may be linked to hypertrophy in HCM and are more severe in end-stage disease patients, such as those undergoing heart transplantation, than in patients referred for myectomy [ 62 ].…”
Section: Pathophysiological Mechanisms Of Ischaemia In Hcmmentioning
confidence: 99%